Mendorong Pengembangan Kewirausahaan Islam Dan Kemandirian Siswa Di SMA Al-Jamiyatul Washliyah - Fauziah Naira; Mutiara Siahaan; Hastrina Novasari; Mutia Sari Devi; Nazira Novrismi (CV. Armas Suan Sejahtera, 2025)
The development of Islamic entrepreneurship in senior high schools (SMA) is a strategic step in building the economic independence of the younger generation and strengthening the local economy based on sharia values. This study aims to analyze the implementation of a community service program in the form of Islamic entrepreneurship training at SMA Al-jamiyatul Washliyah and its impact on increasing students' economic independence and creativity. The research method used a descriptive qualitative approach with observation, interviews, and documentation techniques during the service activities. The results show that the sharia-based entrepreneurship program is able to improve students' understanding of Islamic economic principles, foster an entrepreneurial spirit, and encourage the development of small businesses based on local potential. In addition, this program also has a positive impact on increasing sharia financial literacy and awareness of Islamic business ethics among students. This study concludes that the integration of Islamic entrepreneurship in secondary education plays a crucial role in shaping a young generation that is independent, innovative, and oriented towards sustainable local economic development.